"Helicobacter pylori in familial mediterranean fever: A series of 120 patients from literature and from france". Issue 2 (15th February 2021) - Lacout, Carole; Savey, Léa; Bourguiba, Rim; Giurgea, Irina; Amselem, Serge; Hoyeau, Nadia; Galland, Joris; Amiot, Xavier; Grateau, Gilles; Ducharme‐Bénard, Stéphanie; Georgin‐Lavialle, Sophie
Abstract: Introduction: Familial Mediterranean Fever (FMF), the most common monogenic auto‐inflammatory disease, is characterized by recurrent febrile abdominal pain. Helicobacter pylori infection (HPI), one of the most frequent infections worldwide, can mimic an FMF attack. Objectives: Identify FMF patients with HPI in a cohort of French FMF patients and the literature and identify features allowing to distinguish HPI from an FMF attack. Methods: A retrospective study of all HPI cases was performed on the cohort of FMF patients fulfilling the Livneh criteria from the French Reference Center for rare Auto‐Inflammatory Diseases and Amyloidosis (CEREMAIA). A systematic literature review of HPI in FMF patients was conducted according to the PRISMA guidelines. Results: Eight French patients developed HPI, whose symptoms of epigastralgia, diarrhea, anorexia/weight loss, and nausea/vomiting differed from their typical abdominal FMF attacks. A total of 112 FMF patients with HPI have been described in the literature, including 61 adults. Diagnosis of HPI was made by gastroscopy (n = 43), labelled urea test (n = 55) or IgG serology by ELISA (n = 12). When performed, C‐reactive protein was always elevated. Ten cases of interaction between colchicine and antibiotic therapy for HPI (clarithromycin (n = 9) and azithromycin (n = 1)) were reported. Conclusion: We described a total of 120 patients with typical FMF and HPI. When FMF patients develop atypical abdominal symptoms, upper gastrointestinal endoscopy with biopsies is essential to eliminate underlying HPI. Untreated HPI can lead to misdiagnosis of colchicine resistance with inappropriate prescription of an interleukin‐1 inhibitor at a non‐negligible cost.